Ruas de comércio: avenida Cônego João Lima e as vivências laborais de vendedores de confecções em Araguaína – Tocantins - Sousa, Janderson Henrique Mota de (2019)
This dissertation approaches, through the labor-language relationship, what it means to be a garment salesperson at Cônego João Lima Avenue. We have as general and specific objectives, to identify in the enunciations of the survey participants possible vulnerability indicators that trace a correlation with the "uses of itself", concept coming from the ergological approach. We will take as parameter for these possible vulnerability indicators: 1 - regional dynamics, producing the spatializations of trade relations; 2 - the specific implications of each spatialization that will demand from the seller different “uses of itself". The research method that will base this work on, Is the historical method, because we will start from the research material, which, in this case, are the interviews guided by semi-structured script, to proceed to the descriptioninterpretation movement. We hypothesize that, even in the midst of attempts of normalization and re-normalization, performed by the self-body in the disjunction between the prescribed and the real of the activity there is a failure in these attempts, and these failures are in correlation with the clash of opposing forces: the desire / will and the dramatic situation arising from the relations of the work environment. The discussion of antecedent norms becomes inefficient through the disjunction between the prescribed and the real of the activity, affecting the capacity of the sellers’ response in the context of work in the face of unforeseen situations. With an affected ability to respond, negatively, these sellers may present vulnerabilities evidences stemming from society's risks and that give some effects to the work context, which, they are submitted. The research results, as can be seen in the analysis chapter, "Work experiences of sellers", points to an exposure to the risks arising from society and influence directly the sellers’ work context. In addition, as much as they try to (re)normalize a situation, the real of the activity will focus on perverting the norms and demanding distinct "uses of self" from the sellers' body. Some of these different uses are risk incidents, called by the regional dynamics that move commercial relations, at Cônego João Lima Avenue. Moreover, commercial relations when summoned demanded different uses on the sellers’ body, thus linking labor relations that are characteristic of the spatialization 04, which corresponds to the spatialization of the garment sellers.